Organizational Gameplay: The Player as Designer of Character Organizations. (11th May 2015) - Coutinho, Luciano R.; Galvão, Victor M.; Batista, Antônio de Abreu; Moraes, Bruno Roberto S.; Fraga, Márcio Regis M.
Abstract : Looking at the ways in which players interact with computer games (the gameplays ), we perceive predominance of character-centered and/or microcontrolled modes of interaction. Despite being well established, these gameplays tend to structure the games in terms of challenges to be fulfilled on an individual basis, or by thinking collectively but having to microcontrol several characters at the same time. From this observation, the paper presents a complementary gameplay in which the player is urged to face collective challenges by designing character organizations . The basic idea is to make the player structure and control group of characters by defining organizational specifications (i.e., definitions of roles, collective strategies, and social norms). During the game, commanded by the player, artificial agents are then instantiated to play the roles and to follow the strategies and norms as defined in the organizational specification. To turn the idea into practice, the paper proposes an abstract architecture comprising three components or layers. This architecture is materialized in a proof of concept prototype that combines the Minecraft game server, JADE agent platform, and MOISE+ organizational model. Variations and possibilities are discussed and the proposal is compared to related work in the literature.